Państwowy i społeczny nadzór nad warunkami pracy - Stolarz, Aneta (My University, 2014)
Ochrona pracy jest obowiązkiem wyspecjalizowanych organów państwowych, które wykonują te zadania współpracując z instytucjami społecznymi. Nadzór nad warunkami pracy poszczególnych organów i instytucji wynika z ich zakresu działania, zadań, uprawnień i funkcji - co zostało przedstawione w niniejszej pracy licencjackiej. System ochrony pracy daje gwarancje prawne mające na celu przeciwdziałanie zagrożeniom dla zdrowia i życia ludzkiego w procesie pracy.

The supervision of working conditions is a responsibility of specialised state organs cooperating with various social institutions. These bodies supervise working conditions through their activities, duties, functions and authority – which has been scrutinised in this thesis. The system of supervision of working conditions is guaranteed by the laws protecting employees against life and health hazards which may occur during work process.
State and Social Supervision of Working Conditions
Keywords: ochrona pracy; organy państwowe; instytucje społeczne; nadzór; warunki pracy; współpraca; protection at work; state organs; social institutions; supervision; working conditions; cooperation